Mastectomy with skin preservation and immediate reconstruction by approach periareolar: a new therapeutic alternative - Aizen, Bernardo; Chifflet, Alvaro; Simonet, Fernando; Ventos, Alvaro; Lamas, María; Viera, Richard; Vespa, Mauricio; Núñez, Mercedes; Melgarejo, G (Cirugía del Uruguay, 1999)
The indications, technica/ aspects and results of skin sparing mastectomy, with inmediate breast reconstruction are described. The method is proposed far the treatment of early breast cancers that are not candidates far breast conservation due to its satisfactory oncologic and reconstructive outcome. The periareolar aproach allows mínimum scar sequelae, which is camouflaged by the reconstructed nipple-areola complex